2019
DOI: 10.1063/1.5128148
|View full text |Cite
|
Sign up to set email alerts
|

Type-II heterostructures of α-V2O5 nanowires interfaced with cadmium chalcogenide quantum dots: Programmable energetic offsets, ultrafast charge transfer, and photocatalytic hydrogen evolution

Abstract: We synthesized a new class of heterostructures by depositing CdS, CdSe, or CdTe quantum dots (QDs) onto α-V2O5 nanowires (NWs) via either successive ionic layer adsorption and reaction (SILAR) or linker-assisted assembly (LAA). SILAR yielded the highest loadings of QDs per NW, whereas LAA enabled better control over the size and properties of QDs. Soft and hard x-ray photoelectron spectroscopy in conjunction with density functional theory calculations revealed that all α-V2O5/QD heterostructures exhibited Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…The resulting charge-separated states need to be long-lived and the separated electrons/holes further need to be rapidly transported along potential gradients to catalytic sites to mediate redox reactions . Staggered, type-II, band alignments are particularly desirable to drive rapid interfacial charge separation of photogenerated electrons and holes and to enable their localization at opposite ends of binary heterostructures. Interfacing MoS 2 with other semiconductor nanocrystals provides a means to tune interfacial energetic offsets and charge transfer dynamics, thereby enabling electron injection and effective solar energy conversion. ,, As an example of this approach, Hong et al have demonstrated that upon photoexcitation of MoS 2 /WS 2 heterostructures, charge separation is achieved within 50 fs, enabling a substantially increased photocurrent density and incident-photon-to-current-efficiency in a photovoltaic device. , II–VI semiconductors are attractive candidates for coupling with MoS 2 by dint of their high absorption cross sections in the visible region of the electromagnetic spectrum and the size and compositional tunability of their bandgaps. , …”
Section: Introductionmentioning
confidence: 99%
“…The resulting charge-separated states need to be long-lived and the separated electrons/holes further need to be rapidly transported along potential gradients to catalytic sites to mediate redox reactions . Staggered, type-II, band alignments are particularly desirable to drive rapid interfacial charge separation of photogenerated electrons and holes and to enable their localization at opposite ends of binary heterostructures. Interfacing MoS 2 with other semiconductor nanocrystals provides a means to tune interfacial energetic offsets and charge transfer dynamics, thereby enabling electron injection and effective solar energy conversion. ,, As an example of this approach, Hong et al have demonstrated that upon photoexcitation of MoS 2 /WS 2 heterostructures, charge separation is achieved within 50 fs, enabling a substantially increased photocurrent density and incident-photon-to-current-efficiency in a photovoltaic device. , II–VI semiconductors are attractive candidates for coupling with MoS 2 by dint of their high absorption cross sections in the visible region of the electromagnetic spectrum and the size and compositional tunability of their bandgaps. , …”
Section: Introductionmentioning
confidence: 99%
“…These heterostructures have type-II interfaces that drive electron transfer from photoexcited CdSe to the conduction band of α-V 2 O 5 . 29 The chargeseparation mechanism at the α-V 2 O 5 /CdSe interface, QD-to-NW electron transfer, is thus the reverse of the mechanism for M x V 2 O 5 /QD heterostructures. Under prolonged illumination of dispersions, HER from LAA-derived α-V 2 O 5 /CdSe was 20-fold more efficient relative to colloidal cys-CdSe QDs, illustrating that interfacial charge separation indeed promotes redox photocatalysis.…”
Section: Photocatalysismentioning
confidence: 99%
“…We attributed the slower HER at SILARderived α-V 2 O 5 /CdSe heterostructures to rapid electron−hole recombination at interfaces with direct contact between CdSe and α-V 2 O 5 , whereas, for LAA-derived heterostructures, the presence of cysteine as a molecular linker further separates electrons and holes and provides a barrier to recombination. 29 In an effort to eliminate the need for solvated cocatalyst, and toward the goal of preparing ternary heterostructure photocatalysts, we have recently synthesized MoS 2 /CdS heterostructures, via SILAR deposition of CdS onto MoS 2 nanoplatelets, and characterized their electronic structure, excitedstate charge-transfer reactivity, and photocatalytic performance. 30 with Faradaic efficiency approaching 100% (Figure 8E).…”
Section: Photocatalysismentioning
confidence: 99%
See 2 more Smart Citations